ANALISIS UJI KAUSALITAS PENERIMAAN PAJAK DAN PENGELUARAN PEMERINTAH DI KOTA SURAKARTA DENGAN MENGGUNAKAN METODE GRANGER TAHUN 1978-2003 - Indrawati, Sarastika; Soebagiyo, Daryono (Universitas Muhammdaiyah Surakarta, 2006)
This research aim is to analyse relation pattern between tax income (Tx) with government expenditure (G) in Surakarta. Referring to that made hypothesis that tax income have causality with government expenditure.This research uses time series data with period of year 1978 - 2003. Analysis result mention that there is causality unidirectional/one way pattern of tax income to government expenditure in Surakarta. It is mean that the increasing of tax income push government expenditure. But, the increasing of government expenditure will not push tax income in Surakarta.